1987
DOI: 10.1172/jci113176
|View full text |Cite
|
Sign up to set email alerts
|

Transient elevation of messenger RNA encoding gastrin-releasing peptide, a putative pulmonary growth factor in human fetal lung.

Abstract: Gastrin-releasing peptide (GRP), the mammalian homologue of the amphibian peptide bombesin, is present in pulmonary neuroendocrine cells and appears to be a growth factor for both normal and neoplastic pulmonary cells. Previously we have reported the cloning of the messenger RNAs (mRNAs) and gene that encode human GRP. We now report that GRP mRNAs are markedly elevated in human fetal lung during the canalicular phase of pulmonary development (from -16 to 30 wk gestation). By RNA blot and in situ hybridization … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
60
0
5

Year Published

1992
1992
2000
2000

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 125 publications
(69 citation statements)
references
References 31 publications
4
60
0
5
Order By: Relevance
“…That CD10/NEP inhibition similarly stimulates e 18 fetal lung growth and maturation is consistent with these observations. CD10/NEP inhibition has the greatest effects on fetal lung growth and maturation during the time frame in which endogenous fetal lung CD1O/NEP transcript levels are most abundant (-e [16][17][18]. Although SCH32615 administration in utero from e 12-14 had little effect on e 14 lung growth, significantly greater effects were seen at e 16-18. Similarly, SCH32615 administration from e 15-17 markedly enhanced e 18 fetal lung development.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…That CD10/NEP inhibition similarly stimulates e 18 fetal lung growth and maturation is consistent with these observations. CD10/NEP inhibition has the greatest effects on fetal lung growth and maturation during the time frame in which endogenous fetal lung CD1O/NEP transcript levels are most abundant (-e [16][17][18]. Although SCH32615 administration in utero from e 12-14 had little effect on e 14 lung growth, significantly greater effects were seen at e 16-18. Similarly, SCH32615 administration from e 15-17 markedly enhanced e 18 fetal lung development.…”
Section: Discussionmentioning
confidence: 99%
“…In recent studies, these peptides were also shown to stimulate the proliferation and maturation of normal fetal lung. Gastrin-releasing peptide (GRP; mammalian bombesin) transcripts and immunoreactivity were detectable in pulmonary neuroendocrine cells of human fetal lung as early as 8 wk gestation, with peak transcript levels occurring at midgestation ( 17). In murine fetal lung, maximal GRP expression occurred on embryonic days 17 and 18 (e 17-18).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…BLP have also been implicated in normal fetal lung development (28,29). GRP mRNAs were first detected in human fetal lung at 9-10 wk gestation, peaked at 16-30 wk at levels 25-fold higher than in adult lungs, and subsequently declined to near adult levels by 34 wk gestation (28).…”
Section: Introductionmentioning
confidence: 99%
“…Traditionally, GRP is known for the ability to stimulate the release of gastrin and other gastrointestinal hormones in the gut (see Bunnett 1994 for a review). GRP is also found in the brain (Lynn et al 1996), in pulmonary endocrine cells of the foetal lung (Spindel et al 1987) and is produced by a variety of human tumours (Preston et al 1996). Mitogenic effects of GRPlike peptides have been demonstrated for a number of different cell types, including Swiss 3T3 fibroblast cells (Zachary & Rozengurt 1985), ovine foetal chondrocytes (Hill & McDonald 1992) and human endometrial stromal cells in culture (Endo et al 1991).…”
Section: Introductionmentioning
confidence: 99%